Exploring the antecedents of customers’ willingness to use service robots in restaurants. - Molinillo-Jiménez, Sebastián; Rejón-Guardia, Francisco; Anaya-Sánchez, Rafael (My University, 2023)
This study examines the willingness of customers to accept, and their intention to recommend, the services provided by service robots in restaurants. A mixed-methods research approach was taken to evaluate a theoretical model based on behavioural reasoning theory (BRT). The results demonstrated the important influence of positive attitudes and objections to the use of service robots on consumers’ willingness to use service robots, as well as their intention to recommend restaurants that use them. Among the main aspects that affect attitudes and objections, we found hedonic perceptions, perceived safety, interaction quality perception and anthropomorphism.
Keywords: Autómatas; Service robots; Willingness to accept; Intention to recommend; Objections to use; Interaction quality perception; Perceived safety; Anthropomorphism